2001
DOI: 10.1016/s0042-6989(01)00175-4
|View full text |Cite
|
Sign up to set email alerts
|

Flanker effects in peripheral contrast discrimination—psychophysics and modeling

Abstract: We studied lateral interactions in the periphery by measuring how contrast discrimination of a peripheral Gabor patch is affected by flankers. In the psychophysical experiments, two Gabor targets appeared simultaneously to the left and right of fixation (4 degrees eccentricity). Observers reported which contrast was higher (spatial 2-alternative-forced-choice). In different conditions, Gabor flankers of different orientation, phase, and contrast were present above and below the two targets, at a distance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
55
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 56 publications
10
55
1
Order By: Relevance
“…This is not to say that the possibility of response bias is ignored in existing work. Indeed, in most work, investigators have been exceedingly careful to balance response alternatives in order to minimize the potential effects of response bias (Dosher & Lu, 1999;Lu & Dosher, 2004;Zenger-Landolt & Koch, 2001). Unfortunately, with respect to questions of detection, those alternatives typically have not included the complete absence of the critical stimulus property (i.e., the target property has always been present on each trial).…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that the possibility of response bias is ignored in existing work. Indeed, in most work, investigators have been exceedingly careful to balance response alternatives in order to minimize the potential effects of response bias (Dosher & Lu, 1999;Lu & Dosher, 2004;Zenger-Landolt & Koch, 2001). Unfortunately, with respect to questions of detection, those alternatives typically have not included the complete absence of the critical stimulus property (i.e., the target property has always been present on each trial).…”
Section: Discussionmentioning
confidence: 99%
“…Since Polat & Sagi (1993) first demonstrated both facilitation and suppression with such an arrangement, a multitude of spatial (Polat & Sagi 1994;Polat 2009;Polat et al 1998;Zenger-Landolt & Koch 2001;Mizobe et al 2001;Freeman et al 2001;Woods et al 2002;Freeman et al 2004;Giorgi et al 2004;Polat et al 2005;Polat & Sagi 2007;Shani & Sagi 2005;Huang et al 2006;Huang & Hess 2007;Huang et al 2012;Huang & Hess 2008;Sterkin et al 2008;Katkov & Sagi 2010;Wu & Chen 2010;Kéita et al 2011;Lev & Polat 2011;Jachim et al 2015) and temporal (Tanaka & Sagi 1998;Polat & Sagi 2006;Cass & Alais 2006;Huang & Hess 2008;Sterkin et al 2009;Li et al 2010;Sterkin et al 2012) combinations of target and flanker designs have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of the early psychophysical studies used large grating targets with coextensive masks and therefore tended to confound the effects of overlay and surround suppression. Most recent contrast threshold measurements in the fovea have found that adjacent targets enhance contrast sensitivity (Polat and Sagi, 1993;Yu et al, 2003), whereas studies in the periphery have noted that adjacent targets suppress sensitivity (Chubb et al, 1989;Solomon et al, 1993;Wilkinson et al, 1997;Snowden and Hammett, 1998;Xing and Heeger, 2001;Zenger-Landolt and Koch, 2001). We asked whether there are two distinct suppressive mechanisms in human vision and whether they are consistent with the neurophysiological suppression mechanisms.…”
Section: Introductionmentioning
confidence: 99%